2012
DOI: 10.1093/cid/cis027
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin for Surgical Prophylaxis?

Abstract: The increasing prevalence of methicillin-resistant Staphylococcus aureus (MRSA) has resulted in a reevaluation of the role of vancomycin for surgical prophylaxis. Two systematic reviews of randomized control studies have concluded that cephalosporins are as effective as vancomycin for the prevention of surgical site infections (SSIs). However, most of these studies were conducted more than 10 years ago and cannot be generalized to the current rates of MRSA. Several time-series analyses have recently evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 40 publications
5
50
0
1
Order By: Relevance
“…This is important, because as observed by Gupta et al [11], vancomycin is associated with an increase in surgical site infections in non-MRSA carriers but not in MRSA carriers. An extensive review of this subject was conducted by Crawford et al [32], who observed that “…the suspected weaker activity against MSSA” has been one of the factors in preventing the routine use of vancomycin for preoperative prophylaxis.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important, because as observed by Gupta et al [11], vancomycin is associated with an increase in surgical site infections in non-MRSA carriers but not in MRSA carriers. An extensive review of this subject was conducted by Crawford et al [32], who observed that “…the suspected weaker activity against MSSA” has been one of the factors in preventing the routine use of vancomycin for preoperative prophylaxis.…”
Section: Reviewmentioning
confidence: 99%
“…Even though MRSA has been observed to have a higher mortality and a longer length of treatment than MSSA [32], MSSA is an important pathogen and has been observed to be an important causative organism in hip and knee arthroplasty [15]. If MSSA is detected preoperatively, eradication prior to elective surgery has been observed to reduce surgical site infections [33].…”
Section: Reviewmentioning
confidence: 99%
“…Although vancomycin has proven pharmacologic efficacy against MRSA, it has no activity against gramnegative aerobes or anaerobes and must be used in combination with traditional prophylactic agents to provide complete coverage [11]. Additionally, the effectiveness and superiority of the addition of vancomycin to the standard prophylactic regimen in infection prevention continues to be debated [33,36,37,39].…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin is a broad-spectrum antibiotic known to be effective against the USA300 strain of MRSA (80), the same strain used in our studies. It is used selectively prior to surgery (54), as it has been suggested to induce renal toxicity; however, this is not known to happen after single-dose administration (81). Vancomycin has also been shown to increase mast cell degranulation (82), which is associated with delayed-type hypersensitivity and renal toxicity (83).…”
Section: Discussionmentioning
confidence: 99%
“…Because the risk of hospital-acquired infection increases as a result of surgery or prolonged stay (such as in intensive care units), patients generally receive prophylactic doses of antibiotics prior to undergoing any procedure (50)(51)(52)(53). Vancomycin is a broad-spectrum antibiotic that is sometimes given as prophylaxis before surgery (54,55). To assess whether the administration of vancomycin could effectively reduce the pathologies observed in animals exposed to propofol and infected with MRSA, mice were treated with vehicle alone, propofol alone, or vehicle or propofol plus a prophylactic single intravenous dose of vancomycin 24 h prior to tail vein infection with MRSA.…”
mentioning
confidence: 99%